Estimating the Water and Carbon Footprints of Growing Avocados in the Munich Metropolitan Region Using Waste Heat as a Water-Energy-Food Nexus Potential - Becker, Lukas; Gondhalekar, Daphne (Frontiers in Sustainable Food Systems, 2022)
Avocados, which have been labeled a superfood and are very popular around the world, are often grown in areas with water scarcity and have long-distance transports to their end consumer. Water and carbon footprints could be reduced by using greenhouse farming, waste heat and rainwater. This study aims to determine whether avocados and other exotic fruits could be locally or regionally grown in greenhouse systems in Bavaria heated using waste heat and examines whether this approach decreases the resulting water and carbon footprints. To test these hypotheses, the waste heat potential is estimated by analyzing a database provided by the Bavarian Environment Agency. Data on water and carbon footprints are extracted from databases by The Water Footprint Network and FAOSTAT. As a local case study, a greenhouse system using waste heat of a nearby glass factory in Upper Franconia is considered. The results show a tremendous waste heat potential for Bavaria and Munich with reduced carbon, but similar water footprints compared to international avocado production. The required area for these avocado farms would only amount to 0.016 percent of Bavaria’s or 0.02 percent of Munich’s total area. With more uncomplicated handling and earlier fruit bearing, fruits like papaya, guava, or carambola seem to be better suited for greenhouse farming than avocados. Waste heat supported farming in controlled environments can require significantly less water through modern irrigation techniques and should be considered when designing new food security concepts for urban or rural areas.